Analysis on Queue System at Vitka Point Gas Station Number 14.294.722 on Motorcycle Line with Pertalite-Based Fuel - Bima Wahyu Pratama; Fandy Bestario Harlan; Adhitomo Wirawan; Asadian Puja Enggita (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to find out the performance of the queuing system at SPBU 14.294.722 Vitka Poin, Batam City on Pertalite fuel for motorcycles. The performance of the queuing system was analyzed to whether it has reached the optimal level. The data were collected through interviews and observations. Then, the obtained data were analyzed using a single line queuing system (single-channel, single-phase). The study used quantitative data in which the calculation was assisted by the "POM-QM Queuing Analysis" software. Based on the result of the single-channel single-phase analysis, the performance of the queuing system applied by the 14.294.722 Vitka Poin, Batam City gas station is optimal. It is because the server utilization level or the average operator's busyness level for 7 days is 72.11 %, and the remaining 27.89% of the busy time is idle time, which is the time when the service is not performed. Meanwhile, the effectiveness of performance at the 14.294.722 Vitka Poin, Batam City gas stations is quite good by referring to the average time required by customers in the queue which is only 0.0139 hours or 0.8322 minutes, and the time required by customers in the system is 0.0192 hours or 1.1541 minutes, and the average number of customers waiting in the queue is only 1.846 or 2 people and the average number of customers waiting in the system is 2.5857 or 3 people. The results indicate that there is no need for additional servers as the performance of using 1 server is quite good.